Visual Communication Strategy in Parody Content: Lessons from the GUSDURian Network - Habibi, Muhamad Lutfi; Rahmadani, Aida Husna; Damayanti, Putri Risqi (Universitas Ciputra, 2025)
The parody of political figures is standard in democratic countries, including Indonesia. However, in Indonesia, some cases of political parodies have faced intense backlash, even leading to legal action. In contrast, the parody of Indonesia's fourth president, Abdurrahman Wahid (Gus Dur), created by the GUSDURian Network, is often presented uniquely and eccentrically. This article provides recommendations for strategic communication practitioners, mainly social media activists, to disseminate the thoughts of prominent Indonesian figures through visual political parodies, with a case study on Gus Dur parody content produced by the GUSDURian Network. Based on in-depth interviews with GUSDURian staff and guided by communication strategy indicators from Onong Uchjana Effendy, this study identifies key strategies for creating accessible, humorous, and responsible parody content. These strategies include targeting Millennials and Generation Z (MZ) fans of anime pop culture, utilizing visually engaging social media platforms, positioning parody content as an initial engagement tool (bait), aligning content with current issues, and verifying content with experts before publication.